2021
DOI: 10.1111/ene.14693
|View full text |Cite
|
Sign up to set email alerts
|

The APOE ε4 allele in relation to pre‐ and postsurgical cognitive functioning of patients with primary brain tumors

Abstract: Background Recent studies suggest a relationship between the APOE ε4 allele and cognitive outcome in patients treated for malignant brain tumors. Still, longitudinal investigations that include a pretreatment cognitive assessment are lacking and APOE’s effects in patients with benign tumors are understudied. This study investigated presurgical cognitive performance and postsurgical change in ε4‐carrying and non‐carrying patients with glioma and meningioma. Methods Neuropsychological test scores (CNS Vital Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Of all studies that reported information on methods for correction for practice effects, 30% ( k = 8/27) applied correction for practice effects (11% standardized regression-based change scores ( k = 3), 23 , 26 , 30 4% alternate testing forms ( k = 1), 19 15% reliable change index ( k = 4), 25 , 28 , 37 , 42 respectively). Fifty-one percent reported whether they had corrected scores for covariates (age, education, and/or gender).…”
Section: Resultsmentioning
confidence: 99%
“…Of all studies that reported information on methods for correction for practice effects, 30% ( k = 8/27) applied correction for practice effects (11% standardized regression-based change scores ( k = 3), 23 , 26 , 30 4% alternate testing forms ( k = 1), 19 15% reliable change index ( k = 4), 25 , 28 , 37 , 42 respectively). Fifty-one percent reported whether they had corrected scores for covariates (age, education, and/or gender).…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies have found genetics to influence cognitive outcomes. One study of 505 patients with HGG, LGG, or meningiomas found that carriers of the APOE ϵ-4 allele (mean age 54.9 years, SD 13.9 years) did not have an increased risk of pre-treatment cognitive dysfunction or cognitive decline within one year of debulking surgery relative to non-carriers (mean age 55.3 years, SD 13.1 years) ( 150 ). However, this does not exclude the presence of potential late treatment effects.…”
Section: Resultsmentioning
confidence: 99%
“…The current patient samples are described (in part) in previous studies (Meskal et al, 2015;van Loenen et al, 2018;Butterbrod et al, 2019Butterbrod et al, , 2020Butterbrod et al, , 2021De Baene et al, 2019a, 2019bLonkhuizen et al, 2019;Rijnen et al, 2019Rijnen et al, , 2020aRijnen et al, , 2020bvan der Linden et al, 2020;Boelders et al, 2023). This project was part of a study protocol registered at the Medical Ethics Committee Brabant (file number NW2020-32).…”
Section: Conflict Of Interestmentioning
confidence: 99%